FORMULATION AND EVALUATION OF FAST DISSOLVING TABLETS OF VALDECOXIB - Ansari, K Kareemuddin; Sharma, Neeraj (Journal of Biomedical and Pharmaceutical Research, 2018)
Valdecoxib is a selective COX- II inhibitor with anti – inflammatory, analgesic and antipyretic properties. The poor aqueous solubility of the drug leads to variable dissolution rates. In the present study an attempt has been made to prepare fast dissolving tablets of Valdecoxib in the oral cavity with enhanced dissolution rate. The fast dissolving tablets of Valdecoxib was prepared with some carriers (polymers) and super disintegrants such as Polyvinyl Pyrrolidone (PVP), Sodium Carboxy Methyl Cellulose (SCMC), Crospovidone NF and β – Cyclodextrin. The above mentioned all carriers and superdisintegrants were taken in different proportions of 5, 10, and 15%. All the formulations of the fast dissolving tablets of Valdecoxib were prepared by direct compression technique. The blend was examined for Angle of repose, Bulk density, Compressibility index and Hausner’s ratio. The prepared tablets were evaluated for hardness, drug content uniformity, friability, disintegration time and dissolution rate. An effective pleasant testing formulation released 99.88% drug within 10 minutes. The prepared formulations drug release was found to be comparable with the marketed dispersible tablets. Keywords: Fast dissolving tablets, Super-disintegrants, Valdecoxib, Crosspovidone, Sodium Carboxy Methyl Cellulose.